Organizational Citizenship Behavior Training to Strengthen Teamwork Among Interns - Fida Olivia Fairuz; Djudiyah (Kirana Publisher (KNPub), 2026)
This study aimed to examine the effectiveness of Organizational Citizenship Behavior (OCB) training in strengthening teamwork among vocational high school internship students at an animation company. The study employed a quantitative pre-experimental method using a one-group pretest–posttest design. The participants consisted of 13 internship students selected through total sampling. Data were collected using a teamwork questionnaire administered before and after the training intervention. The collected data were analyzed using descriptive statistics and a paired-samples t-test to determine differences between pretest and posttest scores. The findings revealed a statistically significant improvement in teamwork following the training intervention (Mdiff = −2.923, t(12) = −2.576, p = .024). Organizational Citizenship Behavior also increased significantly after the intervention (Mdiff = −9.692, t(12) = −2.646, p = .021). These results indicate that OCB training effectively enhanced participants' collaborative skills and voluntary organizational behaviors. The study concludes that OCB training can serve as an effective human resource development strategy for internship programs, particularly in project-based creative industries where teamwork and collaboration are essential for achieving organizational goals.